Analysis of Alfven eigenmode destabilization in DIII-D high poloidal β discharges using a Landau closure model. (1st June 2018) - Varela, J.; Spong, D.A.; Garcia, L.; Huang, J.; Murakami, M.; Garofalo, A.M.; Qian, J.P.; Holcomb, C.T.; Hyatt, A.W.; Ferron, J.R.; Collins, C.S.; Ren, Q.L.; et al.
Abstract: Alfvén eigenmodes are destabilized at the DIII-D pedestal during transient beta drops in high poloidal β discharges with internal transport barriers (ITBs), driven by n = 1 external kink modes, leading to energetic particle losses. There are two different scenarios in the thermal β recovery phase: with bifurcation (two instability branches with different frequencies) or without bifurcation (single instability branch). We use the reduced MHD equations in a full 3D system, coupled with equations of density and parallel velocity moments for the energetic particles as well as the geodesic acoustic wave dynamics, to study the properties of the instabilities observed in the DIII-D high poloidal β discharges and identify the conditions to trigger the bifurcation. The simulations suggest that instabilities with lower frequency in the bifurcation case are ballooning modes driven at the plasma pedestal, while the instability branch with higher frequencies are low n ( n < 4) toroidal Alfvén eigenmodes nearby the pedestal. The reverse shear region between the middle and plasma periphery in the non-bifurcated case avoids the excitation of ballooning modes at the pedestal, although toroidal Alfvén eigenmodes and reverse shear Alfvén eigenmodes are unstable in the reverse shear region. The n = 1 and n = 2 Alfvén eigenmode activity can be suppressed or minimized if the neutral beam injector (NBI) intensity is lower than the experimental value ( ). In addition, if the beam energy or neutral beam injector voltage is lower than in the experiment ( ), the resonance between beam and thermal plasma is weaker. The and 6 AE activity can not be fully suppressed, although the growth rate and frequency is smaller for an optimized neutral beam injector operation regime. In conclusion, AE activity in high poloidal β discharges can be minimized for optimized NBI operation regimes.